Clinical efficacy of carbon dioxide fractional laser in the early treatment of scars after primary cleft lip surgery - WU Min; YIN Heng; HUANG Hanyao; SHI Bing; LI Chenghao (Kouqiang hemian waike zazhi)
[Objective:] To evaluate the clinical effect of carbon dioxide fractional laser in early treatment of postoperative scar of primary cleft lip. [Methods:] A total of 24 children who had undergone primary cleft lip repair in the treatment group were treated with carbon dioxide fractional laser within three months after operation, and 24 children who had undergone primary cleft lip repair in the control group were not treated with laser after operation. Based on the subjective assessment by comparing photographs before and after the treatment and the objective assessment using Vancouver scar scale (VSS) scoring method, the scar conditions of the two groups were compared one year after laser therapy. [Results:] The total effective rate of the treatment group was 91.7% after the completion of the whole course of 4 treatments after 1 year, and the difference between the two groups was statistically significant (P<0.05). The objective assessment results showed that the difference between the two groups was statistically significant (P<0.05). [Conclusion:] Carbon dioxide fractional laser is effective in the early treatment of postoperative scar of primary cleft lip, which is worthy of clinical application.